(untitled) (Bangladesh Journal of Urology, 2020)
Objective: This study aims to evaluate the outcomes of PCNL without JJ ureteric stent in comparison to PCNL with JJ ureteric stent. Patients and Methods: This observational study intended to compare the outcome between PCNL without JJ stent and PCNL with JJ stent of 50 cases of renal stone disease according to the inclusion and exclusion criteria and randomly assigned to Group - A (PCNL without JJ stent) and Group - B (PCNL with JJ stent). This study was conducted in the department of urology, Dhaka Medical College Hospital from July 2014 to June 2016. During postoperative period, both groups were compared with respect to fever, loin pain, dysuria, frequency of micturation, duration of haematuria, continuation of urine leakage, hospital stay, urinoma and hematoma and urinary tract infection. Results: Among the 50 patients, the mean postoperative hospital stay was significantly longer in PCNL with JJ stent (4.48 ± 2.14 days) than that of PCNL without JJ stent (2.60 ± 0.50 days). The continuation of urine leakage at the site of percutaneous tract was also significantly longer in PCNL with JJ stent than in PCNL without JJ stent (10.8 ± 3.18 hours vs 14.14 ± 3.28 hours, P <0.001). Assessment of outcome during 3 weeks showed that out of 25 subjects in Group - B, 9 (36%) loin pain, 8 (32%) dysuria, 8 (32%) frequency of micturition, 4 (16%) haematuria and another 7 (28%) urinary tract infection. None of the subjects of Group - A reported same type of complications. Conclusions: Percutaneous Nephrolithotomy without JJ stent (stentless PCNL) is safe, effective and viable option in a selected group of patients – with stone size d”3 cm, normal preoperative renal function, single percutaneous puncture, minimum bleeding, no perforation of the collecting system, no obstruction and complete clearance of stones, JJ stent may not be required. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.110-117